Pengaruh sistem distribusi air pada cooling pad terhadap performansi evaporative cooling - I Kadek Dwiana; Luh Putu Ike Midiani; I Dewa Gede Agus Tri Putra (Journal of Applied Mechanical Engineering and Green Technology, 2022)
Evaporative cooling works by sucking air from the environment, then the air is in contact with a pad that is dripping with water on the front side of the blower/fan. Water soaks the pad at the top and the rest of these droplets will fall into the water tank below. Water is circulated from the water tank to the top of the pad with the help of a pump. The cold air coming out of the pad will be blown by the blower/fan into the environment, and the cooling process takes place. Data collection was carried out to obtain the performance of the Evaporative Cooling system made from zeolite by measuring the temperature and RH of the air at several positions, namely outside the conditioned room, after passing through the pad and in the conditioned room. Also recorded is air flow velocity, voltage and current from fans and pumps. Two different water distribution conditions were carried out, namely with the spray pad method and the soaked pad method. Data were collected every 10 minutes for 8 hours. Data were collected for 5 consecutive days. The EC system is an alternative air conditioning system that is environmentally friendly and low energy use. Using a cooling pad material that is environmentally friendly and has the ability to stay wet will make the EC system operate properly. The use of zeolite as a cooling pad material with the ability to absorb and store water is a cooling pad material that needs to be considered. It is still necessary to continue to improve the dimensions and pore structure of the zeolite cooling pad in order to improve the water absorption and storage process.